Safety, uptake, and use of a dapivirine vaginal ring for HIV-1 prevention in African women (HOPE): an open-label, extension study. Issue 2 (February 2021) - Baeten, Jared M; Palanee-Phillips, Thesla; Mgodi, Nyaradzo M; Mayo, Ashley J; Szydlo, Daniel W; Ramjee, Gita; Gati Mirembe, Brenda; Mhlanga, Felix; Hunidzarira, Portia; Mansoor, Leila E; Siva, Samantha; Govender, Vaneshree; et al.
Summary: Background: Two phase 3 clinical trials showed that use of a monthly vaginal ring containing 25 mg dapivirine was well tolerated and reduced HIV-1 incidence in women by approximately 30% compared with placebo. We aimed to evaluate use and safety of the dapivirine vaginal ring (DVR) in open-label settings with high background rates of HIV-1 infection, an important step for future implementation. Methods: We did a phase 3B open-label extension trial of the DVR (MTN-025/HIV Open-label Prevention Extension [HOPE]). Women who were HIV-1-negative and had participated in the MTN-020/ASPIRE phase 3 trial were offered 12 months of access to the DVR at 14 clinical research centres in Malawi, South Africa, Uganda, and Zimbabwe. At each visit (monthly for 3 months, then once every 3 months), women chose whether or not to accept the offer of the ring. Used, returned rings were tested for residual amounts of dapivirine as a surrogate marker for adherence. HIV-1 serological testing was done at each visit. Dapivirine amounts in returned rings and HIV-1 incidence were compared with data from the ASPIRE trial, and safety was assessed. This study is registered with ClinicalTrials.gov, NCT02858037 . Findings: Between July 16, 2016, and Oct 10, 2018, of 1756 women assessed for eligibility, 1456 were enrolled and participated in the study. Median age was 31 years (IQR 27–37). At baseline, 1342 (92·2%) women chose to take the DVR; ring acceptance was more than 79% at each visit up until 12 months and 936 (73·2%) of 1279 chose to take the ring at all visits. 12 530 (89·3%) of 14 034 returned rings had residual dapivirine amounts consistent with some use during the previous month (>0·9 mg released) and the mean dapivirine amount released was greater than in the ASPIRE trial (by 0·21 mg; p<0·0001). HIV-1 incidence was 2·7 per 100 person-years (95% CI 1·9–3·8, 35 infections), compared with an expected incidence of 4·4 per 100 person-years (3·2–5·8) among a population matched on age, site, and presence of a sexually transmitted infection from the placebo group of ASPIRE. No serious adverse events or grade 3 or higher adverse events observed were assessed as related to the DVR. Interpretation: High uptake and persistent use in this open-label extension study support the DVR as an HIV-1 prevention option for women. With an increasing number of HIV-1 prophylaxis choices on the horizon, these results suggest that the DVR will be an acceptable and practical option for women in Africa. Funding: The Microbicide Trials Network and the National Institute of Allergy and Infectious Diseases, The Eunice Kennedy Shriver National Institute of Child Health and Human Development, and the National Institute of Mental Health, all components of the US National Institutes of Health.